The Relationality of Ecological Emotions: An Interdisciplinary Critique of Individual Resilience as Psychology’s Response to the Climate Crisis - Kałwak, Weronika; Weihgold, Vanessa (Frontiers in Psychology, 2022)
An increasing number of academic papers, newspaper articles and other media representations from all over the world recently bring climate change’s impact on mental health into. Commonly summarized under the terms of climate or ecological emotions, these reports talk about distress, anxiety, trauma, grief or depression in relation to environmental decline and anticipated climate crisis. While the majority of psychology and mental health literature thus far presents preliminary conceptual analysis and calls for empirical research, some explanations of ecological emotions are already offered. They mainly draw from psychoanalysis and depth existential and humanistic psychology, as well as social psychology and address the relationship between ecological emotions and individual engagement in climate action. While these studies suggest building on individual resilience if concerned by ecological emotions, we argue that this only addresses their acute symptoms and not the (chronic) social causes. Based upon our literature research, we show that in an individualistic society such as the (neo-)liberal ones, feelings of individual responsibility are fostered, and this also applies to climate activism.